THE LATVIAN LANGUAGE IN THE LINGUISTIC LANDSCAPE OF DAUGAVPILS (THE MIDDLE OF THE 19TH CENTURY - TODAY) - Pošeiko, Solvita (Journal of Education Culture and Society, 2020)
This paper will focus on the LL of Daugavpils from a diachronic point of view in order to describe the usage of the Latvian language in the public space since the middle of the 19th century until today, as well as the socio-economic and political factors which influence the language situation. Research sources are old photos which depict legible signboards, and photos obtained during LL research 2013. The role of the Latvian language in public information increased during the first period of independence, when ideas of nationalism become widespread and the first normative documents about language usage were approved. However, the stability of Latvian as the main language of the public was only established during the first Latvian Republican period at the end of the 20th century, when the State Language Law was passed and implemented in linguistic practice. Currently, the linguistic landscape reflects the political, socio-pragmatic, and social identity motivations of the owners of public texts, but within the confines of the restrictions imposed by language laws.